PNF in Practice An Illustrated Guide - Adler, Susan S.; Beckers, Dominiek; Buck, Math.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
PNF (Proprioceptive Neuromuscular Facilitation) is a concept to therapeutic exercise which therapists all over the world have found effective for treating patients with a wide range of diagnoses. The approach presented in this richly illustrated guide is based on the concepts set out by Dr. Herman Kabat and taught by Margaret Knott. The fully revised fourth edition demonstrates how the principles of the International Classification of Functioning, Disability and Health (ICF) and aspects of motor learning and motor control (from (S1(Bhands-on(S0 (Bto (S1(Bhands-off(S0 (Bmanagement) are applied in modern PNF evaluation and treatment. A new fresh fully-coloured design and layout highlights the clearly structured way in which philosophy, basic procedures and treatment patterns of PNF are based. New for this edition -Fully revised introductory chapter on the PNF basics, now including discussion and demonstration of ICF and Motor Learning aspects in detailed case study. -Throughout chapters, new additional case studies that help visualize the application of PNF applications in promoting the patients$1 (Beveryday-life motor skills on activity and participation levels.s
Introduction -- Basic Procedures for Facilitation -- Techniques -- Patient Treatment -- Patterns of Facilitation -- The Scapula and Pelvis -- The Upper Extremity -- The Lower Extremity -- The Neck -- The Trunk -- Mat Activities -- Gait Training -- Vital Functions -- Activities of Daily Living -- Test Your knowledge: Questions and Answers -- Glossary.
Keywords: Medicine; Neurology; Rehabilitation; Occupational Therapy; Physical therapy; Medicine & Public Health; Physiotherapy; Occupational Therapy; Neurology; Rehabilitation